DAMPAK PEMBALAKAN BERWAWASAN LINGKUNGAN (PBL) TERHADAP KERUSAKAN TEGAKAN DAN BIAYA PENYARADAN DI HUTAN PRODUKSI ALAM - Sona Suhartana (Jurnal Penelitian Hasil Hutan, 2002)
This paper deals with the results of study on implementing reduced impact logging (RIL) as well as conventional logging (CL), which was carried out in natural production forest under the concession operation of a forest company in Riau in 2001. The aim of this study was to assess the effect of reduced impact logging on possible improvement or securing the stand damage, level of ground exposure, top soil displacement, and cost related skidding productivity.The data collected in this regard were the number of felled trees (stands), number of trees with the diameter of 20 cm or greater, number of damaged trees and poles, ground exposure, top soil displacement, skidding cost, and skidding productivity. The data as such consisted of two main categories, i. e. the one and the other one that resulted consecutively from the implementation of RIL and CL systems. The two-category data were analyzed with respect to their possible differences using at-test.Results of study revealed that the implementation of RIL system brought out more convenient impacts in comparison to the CL, as follows: (1) Level of tree (stand) damage would decrease by about 5.4% (highly significant); (2) Ground exposure decreased by around 9 percent (significant); (3) the decrease in top soil displacement by about 2.4 mm (highly significant); (4) Skidding cost decreased by some Rp 398.98 per m3. With respect to skidding productivity using RIL (compared to CL), there was apparently an increase by about 2.6 m3 per hour. However, such an increase was not significantly different.Based on environmental, technical and economical considerations, the RIL system for future logging operation can be recommended in preference to the CL.